EFFECTIVENESS OF RECTAL MISOPROSTOL IN CESSATION OF POST PARTUM HAEMORRHAGE: Rectal Misoprostol in PPH - Nasreen, Dr Samia; Baqai, Shehla; Iftikhar, Bushra; Bukhsh, Sumaira; Kamran, Muhammad (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the efficacy of rectal misoprostol in management of Post Partum Haemorrhage in third stage of labour. Study Design: Interventional study. Place and Duration of Study: Gynaecology and obstetrics department at PNS Shifa Hospital Karachi, from Sep 2012 to Mar 2013. Material and Methods: All singleton and multiple pregnancies of gestation 37-42 weeks, who presented in labour room to deliver and had prolonged second stage of labour (n=112) were enrolled in the study. Patients, who were having coagulopathy, abruption, placenta previa, and allergy to prostaglandins were excluded from the study. Third stage was managed actively according to hospital standard routine. Hemoglobin was measured at the time of admission and repeated after delivery in patients having PPH. Blood was estimated by weighing all gauzes and packs. If blood loss more than 500ml one hour after delivery and all traumatic causes and retained placenta were excluded, 600μg (3 tablets) of misoprostol were given per rectally, which were inserted up to a digit depth. After one hour total amount of blood loss was calculated. The data were then entered in a proforma and analyzed. Results: Majority (44.6%) of the women were 26-33 years of age, 8.9% had PPH with fall in hemoglobin by 1.5-2 gms/dl. Ninety percent of the patients responded to rectal misoprostol. Conclusion: Active management of third stage of labour has a definite role in the preventive of PPH. Rectal administration of misoprostol should be considered for control of PPH in low resource settings like ours as it was found effective in the study.